Factors Affecting the Success Rate of External Dacryocystorhinostomy at B. P. Koirala Institute of Health Sciences, Dharan, Nepal - Pokharel, Shailesh Mani; Chaudhary, SK; Chaurasiya, BD (Birat Journal of Health Sciences, 2017)
Introduction Any disturbance to the normal ouVlow of tears through the nasolacrimal passage causes overﬂow known as epiphora. The clinical symptoms of epiphora range from mild dribble to the continuous ouVlow of tears. Watering of eyes caused by the nasolacrimal drainage obstruction is managed by surgery. One of the many surgeries to treat this is external dacryocystorhinostomy. Objective The objective of this study was to evaluate the success rate of external dacryocystorhinostomy as well as factors aﬀecting it. Methodology This is a retrospective cross-sectional study, conducted in the Department of Ophthalmology, B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan with the approval of Institutional Review Committee, BPKIHS. The medical records of patients who underwent external Dacryocystorhinostomy surgery from April 2011 to April 2016 at BPKIHS were retrospectively reviewed. Statistical analysis was performed using SPSS for windows, version 11.5 (SPSS Inc., Chicago, IL). Binary logistic regression models were used to investigate the association of the surgical outcome with various predicting variables. Results The success rate of the external dacryocystorhinostomy was 78.09%. Factors studied were: age, with a range of 2-81 years; duration of symptoms with a range of 1-84 months; and gender of the patients. The intra-operative factors studied were use of silastic tube, types of ﬂap, and osteotomy size. Among these factors, the duration of symptoms and osteotomy size had signiﬁcant association with the outcome of the surgery p<0.05. Conclusion Our study yielded high success rate in patients with shorter duration of watering of eyes and larger osteotomy size during surgery. Hence, a larger osteotomy size and early intervention is recommended for better surgical outcome. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 196-200